Landscape analysis of m6A modification reveals the dysfunction of bone metabolism in osteoporosis mice - Lifeng Zheng; Chao Lan; Xinyue Gao; An Zhu; Yaoqing Chen; Jinluan Lin; Sunjie Yan; Ximei Shen (Heliyon)
Osteoporosis (OP) is a prevalent chronic bone metabolic disorder that affects the elderly population, leading to an increased susceptibility to bone fragility. Despite extensive research on the onset and progression of OP, the precise mechanisms underlying this condition remain elusive. The m6A modification, a prevalent form of chemical RNA modification, primarily regulates posttranscriptional processes, including RNA stability, splicing, and translation. Numerous studies have underscored the crucial functions of m6A regulators in OP. This study aimed to explore the relationship between OP and RNA m6A methylation, investigating its underlying mechanisms through comprehensive bioinformatic analysis and experimental validation. The mRNA sequencing (mRNA-seq) and methylated RNA immunoprecipitation sequencing (MeRIP-seq) were performed on control mice as well as ovariectomized mice to discover differentially expressed genes (DEGs) and m6A regulators in OP. The results revealed dysregulation of a majority of bone metabolism-related genes and m6A regulators in ovariectomized mice, indicating a closely linked relationship between them. Our research findings indicated that m6A modification is essential in regulating OP, offering potential insights for prevention and treatment.